Handlingsrom for profesjonalisert velferd: Kommunale tjenester for helse, omsorg og barnevern - Lind Kassah, Bente Lilljan; Nordahl-Pedersen, Hilde; Tingvoll, Wivi-Ann (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
"How much room to manoeuvre do administrators of municipal social services feel they have in meeting organizational objectives? How much latitude do staff in these services have to utilize their own expertise in performing tasks? What challenges do welfare services face due to cultural diversity? Can new ways of working contribute to increased learning for students in the practice field? These are among the questions addressed in this book, in which challenges associated with maintaining society's objectives in municipal health, care and child welfare services are focused on. The goal is to provide the reader with insight into degree of latitude pratictioners have when seeking to utilize their own expertise in the context of their job. The book is a collection of ten scholarly articles that, via new empirical studies and theoretical contributions, shed light on manoeuvering room within the practical fulfilment of professional welfare services in the two main municipal healthcare and child welfare organizations. Both services must comply with public regulatory measures in an increasingly more complex field; both are therefore examined in the same anthology. Latitude in Professional Welfare Administration is directed primarily toward students in nursing, child welfare and social education, but may be of interest to students in other health and caregiving fields as well. Employees within municipal health and family services including child welfare services, and politicians involved in development within this sector, will also find this anthology useful. The anthology's editors are Bente Lilljan Lind Kassah, professor of sociology at UiT The Arctic university of Norway in Harstad; Hilde Nordahl-Pedersen, assistant professor at UiT The Arctic university of Norway in Harstad; and Wivi-Ann Tingvoll, docent emerita at UiT The Arctic university of Norway in Narvik."